2008
DOI: 10.4161/cc.7.16.6541
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic principles of chromatin remodeling guided by siRNAs and miRNAs

Abstract: Small RNAs can guide chromatin remodeling in mammalian cells, but the mechanisms involved are poorly understood. Previous reports have shown a requirement for overlapping transcription and the involvement of Argonaute (Ago) proteins. Here, we use the Regulatory Domain (RD) of the INK4/ARF locus as an experimental platform susceptible to siRNA-guided chromatin remodeling to interrogate about the mechanisms involved. We show that siRNA-guided chromatin remodeling of RD requires overlapping transcription, and tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 42 publications
1
91
1
2
Order By: Relevance
“…Total RNA was isolated from PB, BM, spleen and other tissues with the Trizol reagent (Invitrogen), and treated essentially as described 48 , using the primers listed in Supplementary Table S2. Gene expression analysis is described in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from PB, BM, spleen and other tissues with the Trizol reagent (Invitrogen), and treated essentially as described 48 , using the primers listed in Supplementary Table S2. Gene expression analysis is described in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP was performed essentially as described 48 . Antibodies for immunoprecipitation were rabbit polyclonals to H3K27me3, H3K9me3, H2Aub1, IgM, Ezh2 and H3K4me3 (all from Upstate; 1:2,500).…”
Section: Chromatin Immunoprecipitation Assaysmentioning
confidence: 99%
“…To complicate the already intricate scenario, it has been recently reported that miRNAs can bind to ribonucleoproteins in a seed sequence and a RISC-independent manner and then interfere with their RNA binding functions (decoy activity) [15] . Three studies have reported that miRNAs can also regulate gene expression at the transcriptional level by direct binding to the DNA [16][17][18].…”
Section: Mirnas Biogenesis and Mechanism Of Actionmentioning
confidence: 99%
“…8,[12][13][14][15][16][17] Certain microRNAs were shown to mediate epigenetic regulation of gene transcription and cell metabolism, the induction of cell death, cell cycle arrest, autophagy, and senescence. 8,[18][19][20][21][22] On one hand, microRNAs were shown to directly bind the gene promoter and gene terminus sequences, thereby modulating specific gene expression at the transcription level. [23][24][25][26] On the other hand, transcriptional deregulation in cancer cells may lead to altered transcription of specific microRNA genes.…”
Section: Introductionmentioning
confidence: 99%